Implantes Oseointegrados : cuatro años de experiencias (1996)
ABSTRACT: The present paper reports four years of experiences in Osseointegrated fixtures, Minimatic of titanium alloy and Lifecore grade 3, pure titanium. 150 Minimatic fixtures and 50 Lifecore/Restore's were placed in 104 patients, 61 women and 43 men, mean age 43.1 years, (range 16-82 years) 107 in the upper and 93 in the lower jaw. From the 200 fixtures inserted, 6 were lost, 4 in the upper and 2 in the lower jaw and 2 were put to sleep, 1 in the maxilla and the other in the mandible for a total failure of 8 screws. The percentage of failure in the maxilla was 4.67% and the success was 95.33%, while in the mandible the failure was only 3.22% and the success 96.78%. 59 single tooth restorations on 59 fixtures were made for 29% of the total amount of implants. 12 overdentures over 27 implants in a 14% of the total fixtures, 33 fixed prostheses over 72 implants for a 36% of the whole number of implants and finally 9 superstructures over 42 fixtures for the last 21% of the implants, 68 bone regeneration procedures previous or during fixture installation were done. Statistical data shows that the total success rate for this study was 96% and failure rate 4%, which allow us to conclude that osseointegration in our hands is a highly, predictable therapy whose results are similar to those presented in different countries.